Artistic Aspects of the Use of Natural Stone in the Architecture of Medieval Novgorod - Antipov, Ilya V. (Actual Problems of Theory and History of Art, 2023)
The main objective of the article is to reveal the correlation of functional, constructive aspects and the artistic component of the Novgorod architecture on the example of studying the features of the use of natural stone in the laying of stone building walls. It has been established that the architects of the St. Sophia Cathedral (mid-11th century) were trying to use the features of the masonry for aesthetic purposes, specifically emphasizing the individual blocks of stone that make up the church. The builders of the 12th – first half of the 13th century, following the functional logic, hid the stone walls behind the plaster while creating the image of a laconic, solid, and monumental church. In the architecture of the late 13th–15th centuries, masonry walls were not covered with plaster, as the aesthetic aspect of the masonry started to play an important role again, although such a decision may have been made, among other things, to save building materials, working effort, and time. Thus, design and function of course have always been very significant for medieval architecture, but the aesthetic aspects also concerned architects and customers. We can definitely say that masonry inherently had a certain artistic value when we look at the St. Sophia Cathedral in Novgorod, but also in the architecture of the late 13th – 15th centuries masonry, obviously, initially had a certain artistic value.